¿Medicina basada en la ciencia o en el ser humano? La Bioética como mediador (2013)
This article is a discusses about the dehumanization in the medical practice and in the physician patient relationship, and how we can change as teachers, our behavior in order to balance health sciences and human sciences, in our daily processes of learning teaching, using Bioethics as a tool in comprehensive education with our students in order to recover human been dignity, through freedom education that encourages human rights, democracy and peace.